Magia sexualis : sex, magic, and liberation in modern Western esotericism - Urban, Hugh B. (University of California Press, 2006)
Sexuality and the occult arts have long been associated in the western imagination, but it was not until the nineteenth century that a large and sophisticated body of literature on sexual magic-the use of sex as a source of magical power-emerged. This book, the first history of western sexual magic as a modern spiritual tradition, places these practices in the context of the larger discourse surrounding sexuality in American and European society over the last 150 years to discover how sexual magic was transformed from a terrifying medieval nightmare of heresy and social subversion into a moder.